WEIGHT TRAINING IN GYMS AS LEISURE TIME PHYSICAL ACTIVITY: THE PRACTITIONER PROFILE - Remus-Cristian VĂIDĂHĂZAN; Iacob HANȚIU (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2015)
It is gratifying that people of all ages turn to exercise to improve physical fitness components. There is growing evidence that a balanced workout program, including a minimum weight training exercises, sufficient flexibility exercises and enough time for relaxation and recovery, provides long-term benefits (McLatchie, 1993). This type of training, practiced regularly, will reduce the risk of injury and illness (Westcott, 1996). “Currently, RT (resistance training) is a modality of exercise recommended for virtually everyone because it has been shown to enhance health, well-being, and performance in clinical, fitness, and athletic populations” (Ratamess Jr., 2012, p. 9). Objective of the study: The objective of this study was to build a profile for participants in weight training that takes place in gyms of Cluj-Napoca. Methods: The research was conducted from 14 August 2013 to 20 August 2014 in Cluj-Napoca’s weight training gyms. The subjects are practitioners of all gyms where weight training is practised, and where we were granted access. 155 practitioners were interviewed. 47.74% refused participation to our study, and 52.26% accepted permission. For each of the 81 subjects was recorded only one session of training. Conclusions: Participation in weight training is done with appropriate frequency. In terms of exercise duration, for most of practitioners, it exceeds the maximum duration of 60 minutes recommended by the American College of Sports Medicine (American College of Sports Medicine, 1990). The small number of participants that correctly identified the muscles included in their workouts can be a signal for fitness instructors and personal trainers to insist more on the transmission of appropriate information needed to apply the principle of conscious participation. Most of practitioners do not give enough importance to periodization because they insert or exclude exercises after starting their training session. The number of sets chosen for the exercises suggests that almost all of our subjects limit to 3-4 sets for every exercise. In terms of planning the execution speed for repetitions, we found none of the practitioners to work with concept of tempo.